2012
DOI: 10.1016/j.jmmm.2011.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Self-organizing magnetic beads for biomedical applications

Abstract: In the field of biomedicine magnetic beads are used for drug delivery and to treat hyperthermia. Here we propose to use self-organized bead structures to isolate circulating tumor cells using lab-on-chip technologies. Typically blood flows past microposts functionalized with antibodies for circulating tumor cells. Creating these microposts with interacting magnetic beads makes it possible to tune the geometry in size, position and shape. We developed a simulation tool that combines micromagnetics and discrete … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Derby [10] did the same for cylindrical permanent magnets or ideal solenoids. Other than in our preliminary work, where we assumed to have partially homogeneity of the external field [11], a full description of magnetic particle movement need to solve all parts j i B ∂ of the gradient force g F [12].…”
Section: Magnetic Particle Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Derby [10] did the same for cylindrical permanent magnets or ideal solenoids. Other than in our preliminary work, where we assumed to have partially homogeneity of the external field [11], a full description of magnetic particle movement need to solve all parts j i B ∂ of the gradient force g F [12].…”
Section: Magnetic Particle Dynamicsmentioning
confidence: 99%
“…They showed that stokes drag is a good approximation for beads in fluids with laminar flow conditions. In our preliminary work the same Stokes drag was used to find the equilibrium position of magnetic particles in magnetic gradient fields [11]. In these molecular dynamics simulations, later on called particle dynamics [17], the hydrodynamics interactions between the particles are neglected, hence complex dynamics in these fluids under various conditions are not fully understood.…”
Section: Hydrodynamicsmentioning
confidence: 99%
“…Recent technologies try to combine the most promising methods for better filter results. In our preliminary work we show how the CTC yield could be increased with a tunable magnetic bead structure [4].…”
Section: Introductionmentioning
confidence: 99%
“…(a) Simulation of blood flow through variable gap (in this case 6µm) to obtain minimum gap size for each blood cell. (b) Circulating tumor cell captured in magnetic bead trap (side and top view) from preliminary work[4].…”
mentioning
confidence: 99%
“…(a) (b) Figure 1: Elastic objects in biomedical applications a) Simulation of blood flow through tunable magneto-active polymer channel [4] b) Circulating tumor cell captured in magnetic bead trap (side and top view) [5] We utilize the lattice-Boltzmann (LB) method for the description of the fluid dynamics and the immersed boundary (IB) method for the description of the immersed objects. The coupling of both methods provides an accurate description of the complete fluid-structure interactions.…”
Section: Introductionmentioning
confidence: 99%